Psychotherapeutic Consultation Services in the Workplace: A Longitudinal Analysis of Treatments and Sick Leave Using Health Insurance Data - Gantner, Melanie; Jarzcok, Marc Nicolas; Schneider, Jürgen; Brandner, Stefan; Gündel, Harald; von Wietersheim, Jörn (Frontiers in Psychiatry, 2022)
Background: Psychotherapeutic consultation services in the workplace (PSIW) have been developed to provide collaborative mental health care for employees. The aim of this study was to analyze participant characteristics, the role of PSIW in treatment courses and the de-velopment of sick leave before and after PSIW start. Methods: Routine data from PSIW and health insurance of N = 155 participants were analyzed descriptively and by means of a mul-ti-level negative binomial regression. Results: 84% of users were male, 72% were diagnosed with a mental disorder. Number of PSIW consultations varied from one to 13 (mean = 4). For 34% of participants, PSIW sessions were sufficient, 33% received a recommendation for outpatient psychotherapy, 20% for inpatient mental health treatment. While recommenda-tions for inpatient treatment displayed a high adherence rate (74%), recommendations for outpatient treatment were followed by 37%. Compared to the period of a half-year before PSIW, sick leave days were reduced from the period of the second half-year after PSIW start and in the subsequent observed half-year periods. Trajectories of sick leave by subgroups showed differences. Conclusions: PSIW is a flexible care offer and results indicate a possi-ble effect of PSIW on sick leave. In future studies, control group designs and inclusion of further variables are needed.